TELERADIOGRAPHIC PARAMETERS IN YOUNG MEN AND YOUNG WOMEN WITH ORTHOGNATHIC OCCLUSION, DETERMINED BY JARABAK METHOD - Vakhovskyi, V.V.; Chaika, V.H.; Zhuchenko, I.I.; Loboda, I.V.; Gunas, I.V. (World of Medicine and Biology, 2021)
Ukrainian young men and young women with orthognathic occlusion have pronounced sex differences for most of the basic teleradiographic characteristics of the skull and almost half of the indicators that can be used to change the parameters of the upper and lower jaws according to Jarabak method (young men have greater values of distances N-S, S-Ar, Ar-Go, Go_Me, N-Go, S-Gn, S-Go, N-Me and S-Go:N-Me ratio; and in young women – larger values of angles Sum and SN-GoGn). The established differences of teleradiographic indicators according to the Jarabak method with normative data for residents of European origin confirm (in young men have greater values of distances S-Ar, Ar-Go, Go_Me and S-Go, angles N-S-Ar, S-N-Pog, Mand1-GoMe and S-Go:N-Me ratio and smaller values of angles Ar-Go-Gn, Sum, N-S-Gn and distance N-Me; in young women have greater values of angles Max1-SN, Mand1-GoMe, distance Ar-Go and S-Go:N-Me ratio and smaller values of distances N-S, N-Me and angles Ar-Go-Gn, Sum) the need to determine regional standards for the correct use of this method in Ukraine.